STRATEGI MENGAJAR GURU DALAM PEMBENTUKAN KARAKTER SISWA YANG BERBASIS KURIKULUM 2013 DI SDN SAI - Aidin (STKIP Al-Amin Dompu, 2023)
The process of developing human resources is very important to sustain the progress of a nation. Because human resources are the basic standard in driving this nation's climate change, one of them with many well-educated intellectuals will certainly increase economically. The basic foundation is education which must be increased and other things the problem of developing natural resources which is adequately measurable. the teacher's strategy in overcoming student problems is still lacking. The implementation of curriculum 13 is not yet relevant to the conditions in SDN Sai. The research method used is. The results of the research are that the teacher's teaching strategy in the formation of curriculum-based student character. The application of teaching methods in the classroom by the teacher is very relevant to school conditions, and other things students can understand the existing material. The learning tools are very complete consisting of syllabus, Learning Implementation Plans and guidebooks.